Evaluasi Implementasi Sistem Pengendalian Intern Pemerintah (SPIP) pada Pemerintah Kota Gorontalo - Ikal Toha; Rio Monoarfa; Mentari Rizki Sawitri Pilomonu (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to find out how the government internal control system (SPIP) is implemented in the Gorontalo city government. This research uses qualitative research methods, the data source used is primary data where this research uses in-depth interview data collection techniques based on the SPIP elements contained in Government Regulation Number 60 of 2008 concerning the government's internal control system. This research examines the control environment in the Gorontalo City Government, highlighting clear policies, high ethical values, and strong commitment in government management. Although significant steps have been taken, there are several aspects that require further attention. Evaluation of the organizational structure, improving communication, and adjusting roles and responsibilities were identified as potential solutions to improve internal control performance. In addition, the importance of information system security is also emphasized as the main focus for continued improvement. Nevertheless, the Gorontalo City Government shows a clear commitment to improving the control system by considering continuous evaluation to ensure efficiency and effectiveness in government tasks. Steps such as risk evaluation, implementing controls, monitoring information systems, and improving communications and information technology infrastructure are proposed as an effort to improve control performance and increase coordination and access to relevant information in the Gorontalo City Government.